Objets, espaces et corps du chercheur - David Scheer (Criminocorpus)
Through very subjective extracts of my field journal and the journey of an ethnographer in prison, this methodological and epistemological article proposes to analyze the notion of "approach" (“démarche” in French) in two steps. The approach as an art of moving, on one side; referring to a particular ethnographic posture and to methodological and ethical questions from a researcher on his fieldwork. The approach as a cognitive process, on the other side; where will be discussed the meaning of the research and the scientific method.